Cervical maturation using mifepristone in women with normal pregnancies at or beyond term. (May 2020) - Hcini, Najeh; Jolivet, Anne; Pomar, Leo; Mchirgui, Ali; Maamri, Fatma; Elcadhi, Youssef; Lambert, Veronique; Carles, Gabriel
Abstract: Objective: The aim of our study was to evaluate the efficacy and safety of oral mifepristone use for cervical ripening and the initiation of labor in women with normal pregnancies at or beyond term. Study design: We conducted a monocentric, prospective, comparative study on the induction of labor in women with an unfavorable cervix after 37 or more weeks of gestation in the Franck Joly Hospital, French Guiana. The immediate induction of labor by mifepristone was compared to expectant management and the induction of labor with routine cervical ripening agents during two consecutive periods. During the first period, patients received mifepristone (600 mg orally at the moment of enrollment) and were evaluated after 48 h. In the second period, patients did not receive any drugs and were evaluated after 48 h of expectant management. Primary outcomes: Spontaneous labor or a Bishop Score ≥6 within 48 h of mifepristone administration. Secondary outcomes: enrollment-induction to delivery interval, rate of failed induction, doses of prostaglandin used, mode of delivery, requirement of oxytocin augmentation, and neonatal outcomes. Results: This study enrolled 231 women, 108 in the first and 123 in the second period undergoing induced labor at term caused by various obstetric conditions. There were no significant differences between groups for age, body mass index, gravida, parity, the initial Bishop Score, scarred uterus, or post-term pregnancy. There were statistically significant differences between the two groups concerning spontaneous labor and/ or a Bishop Score ≥6 within 48 h (p < 10-3) and received doses of misoprostol (p = 0.01). Patients receiving mifepristone were 10 times more likely to be in labor after 48 h of inclusion (RR = 9.98, CI 95 % = [4.47–22.29]). The enrollment-induction to delivery interval was significantly shorter for the mifepristone group (p < 0.001). There were no other differences in mode of delivery, placenta abnormalities or neonatal outcomes. Conclusion: Mifepristone efficiently induced cervical ripening and labor initiation in women with normal pregnancies at or beyond term. It may offer an alternative method to the classic induction especially for patients seeking spontaneous labor.